Multimodal digital extensive reading program: a reflection on literacy movement in madrasah and pesantren - Khoiriyah Khoiriyah; Ach. Faridul Ilmi (Institut Agama Islam Negeri (IAIN) Palangka Raya, Indonesia, 2023)
Over the years, ample studies on diverse school literacy movements have been discussed. However, multimodal digital extensive reading (MDER) has not been fully incorporated into literacy programs in Islamic private school (madrasah) and Islamic boarding school (pesantren). This study attempts to investigate how digital literacy and reading literacy in the form of MDER program in madrasah and pesantren can be deployed to build strong reading habits. This study employed a qualitative case study design. It involved nine novice teacher participants from ten madrasahs and pesantrens, and one supervisor. The data were garnered from the participants' reflective journals, Focus Group Discussions (FGDs), documentation, and interview with the supervisor. The collected data were analyzed using thematic analysis. The results of this study showed three fundamental tenets of the MDER program in madrasah and pesantren: teachers’ efforts, the sustainable collaboration between teachers and students, and a long-term partnership among school members and stakeholders. The result sheds light on how to build a reading habit and digital literacy in madrasah and pesantren. It also implicates the role of leaders’ policy in achieving successful program implementation.